Analysis of the development of Ukrainian repositories - Tarasov, Dmytro; Andrukhiv, Andriy (Видавництво Львівської політехніки, 2012)
The article presents analysis of the development of Ukrainian repositories and contribution of Lviv Polytechnic National University Institutional Repository in the development of Open Access in Ukraine.
Keywords: Open Access; Dspace; institutional repository